Difficulties and Challenges of Translating Legal Texts from English into Arabic - Kawa Mirza Salih (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
It is essential to investigate the field of legal translation further, because translators face real challenges while dealing with law. Law manages our lives; hence it is obvious that the demand for its translation is high. Legal texts create with themselves dilemma and challenges in translation. Therefore, the language of law needs experienced translators, who can decode these complex texts. This paper specifically focuses on problematic issues in English and Arabic translation of legal texts. In order to show the difficulties of the translators, in translating legal texts, some examples are provided. The main aim in this study is to show that some legal concepts are not readily transferrable into the target language. Hence, the legal translator should seek the meeting point between the two legal systems involved. Another main aim is to investigate the characteristics of the legal writings, as that allows translators to avoid possible difficulties and provide a translation of a better quality.